Certification of grain storage units: contextualization on the importance of adopting the technical requirement to identify GMOs - Rabelo, Juliano Caldas; Santos, Nivaldo dos; Rabelo, Kássia Cristina de Caldas; Furquim, Maria Glaúcia Dourado; de Sousa Júnior, José Carlos (Science & Technology Journals, 2025)
This research provides a context for the certification processes in storage units, analyzing the legal instruments used by those units to support the technical requirements for certification. Through bibliographical research, the aim of this study was to correlate the laws, decrees and other instruments that guide the requirements of certification processes with other literature relevant to this subject, containing aspects related to biotechnology, biodiversity and sustainability. There is an explanation for the recommendation by the certification process to adopt the technical requirement of identifying GMOs in certified warehouses, demonstrating the importance of using this tool to separate GMOs from conventional grains. The inherent aspects of soybean production with GMOevents are presented, and that model is compared withthe conventional production model. The production,consumption and safety of GMOs are discussed, in contrastto the decision of some nations to consume conventionallyproduced food. Thus, factors that attest to the factthat GMO food production is safe for society and theenvironment are presented, demonstrating the scientificbasis of some nations that choose to produce and consumefood with GMO events, adopting strict management controlcriteria.
Keywords: external market requirements; herbicide management; certification processes; biodiversity protection